Bidirectional tick transport by migratory birds of the African-Western Palearctic flyway over Turkish Thrace: observation of the current situation and future projection - AKYILDIZ, GÜRKAN (My University, 2023)
This study was carried out at a vital stopover site of migrating birds in the Turkish Thrace, European part of Turkey, on the Mediterranean/Black Sea Flyway. Ticks were collected from the birds captured in the four migration periods, i.e., autumn 2020, spring 2021, autumn 2021, and spring 2022, and identified morphologically. Throughout the study, 10,651 birds from 77 species were examined, and 671 belonging to 34 species were found infested. The infestation prevalence in total birds and the mean number of ticks per infested bird were 6.3% and 3.8 (range: 1–142), respectively. A total of 2573 ticks were collected with the following species distribution and numbers: Ixodes spp. 70 larvae, I. frontalis 1829 larvae, 337 nymphs, and 30 adults, I. acuminatus 16 nymphs and 42 adults, I. ricinus 39 larvae, 141 nymphs, and one adult, Hyalomma spp. seven larvae and 60 nymphs, and Haemaphysalis sp. one larva. Prevalence, intensity, and species distribution of the ticks in birds varied depending on the month, season, year, and species-specific migration phenology of the birds. The results show that precise determination of the tick-borne risk associated with migratory birds for a particular region necessarily requires long-term and comprehensive studies and indicates that anthropogenic climate change and habitat degradation can significantly differentiate the risk by influencing the migration phenology in birds and by making new regions suitable for the establishment of different ticks.
Keywords: Hyalomma rufipes · Mediterranean/Black Sea Flyway · Migrating birds · Season · Tick dispersal · Tick infestation